Mitochondrial Dysfunction and Oxidative Stress: Emerging Insights in Muscle and Cardiovascular Disease Mechanisms - Riou, Marianne; Geny, Bernard (Antioxidants, 2025)
Beyond their role as the “energy powerhouse” of the cell, mitochondria have emerged as essential actors in molecular signaling and determination of cellular fate, particularly through the production of reactive oxygen species (ROS) [...]